History of Relating Logic. The Origin and Research Directions - Klonowski, Mateusz (Logic and Logical Philosophy, 2021)
In this paper, we present the history of and the research directions in relating logic. For this purpose we will describe Epstein’s Programme, which postulates accounting for the content of sentences in logical research. We will focus on analysing the content relationship and Epstein’s logics that are based on it, which are special cases of relating logic. Moreover, the set-assignment semantics will be discussed. Next, the Torunian Programme of Relating Semantics will be presented; this programme explores the various non-logical relationships in logical research, including those which are content-related. We will present a general description of relating logic and semantics as well as the most prominent issues regarding the Torunian Programme, including some of its special cases and the results achieved to date.